Green Synthesis of Silver Nanoparticles and its Antimicrobial, Antioxidant Activity of Drynaria Quercifolia: Pharmaceutical Science-Chemistry - Kanagalatha, Rajagopal; Chinnusamy, Geetha (International Journal of Life Science and Pharma Research, 2022)
Eco Friendly or green synthesis of metal nanoparticles has become an important branch of nanotechnology and due to their large applications, there is a growing commercial demand for nanoparticles. The plant named' Oak leaf fern' belongs to the Polypodiaceae family and is native to India, Southeast Asia., etc. The main objective of the study is to synthesize silver nanoparticles from Drynaria quercifolia and to check its antioxidant and antibacterial activity from synthesized nanoparticles. The phytochemical analysis was carried out for different extract such as methanol extract, ethyl acetate extract and petroleum ether extract. While comparing the three extracts, methanol extract showed the presence of alkaloids, flavonoids, Terpenoids, Saponin and carbohydrates. The Reducing power assay was conducted for methanol extract. The percentage inhibition of free radicals is found to be 632.06µg/ml. In this study, the synthesis of silver nanoparticles using methanol leaf extract of D.quercifolia in an eco-friendly and cost effective way is reported. The use of D.quercifolia leaf extract as a reduction agent from 1 mM silver nitrate has been examined for the synthesis of silver nanoparticles (SNPs) (AgNO3). The synthesized nanoparticles were characterized by UV–Vis (422 nm), FTIR, SEM, and XRD studies. Within 24 hours of the incubation time, silver nanoparticles were synthesized and generated SNPs had an absorption peak of roughly 400 nm in the UV-visible spectrum. The synthesized AgNPs shows good antibacterial activity against Gram negative bacteria as well as Gram-positive. This technique is quick, easy, without any hazardous chemicals such as reducing or stabilizing agents and economical to synthesize SNPs.